Uncivil Societies : A Theory of Sociopolitical Change - Monga, Celestin (2012)
In times of crises, it is always useful to revisit some of the paradigms that underlie collective thinking and action. For nearly 200 years, most social science has relied on the assumption that the emergence of strong and nurturing social capital through a vibrant civil society yields all kind of positive externalities to society. Following intuition and anecdotal observations from Alexis de Tocqueville, a large body of theoretical and empirical research has attempted to confirm that societies strive politically and economically when they are able to build strong non-state actors and community organizations. Many disciplines-mainly political science, economics, law, and international relations-have constructed influential analytical frameworks in support of that general proposition. This paper examines the philosophical foundations of conventional wisdom and observes that it often fails to take into account the dark side of some civil society groups, from the mafia to Al Qaeda. While acknowledging the potential contribution of civil society to the development process, the paper also cautions again the rush to circumvent the state, which sometimes sustains community-based initiatives in poor countries. It suggests the possibility of the production of negative social capital by non-state actors.